G281(P) Transforming neonatal learning in rural cambodia: design of a comprehensive neonatal training programme for midwives, nurses and doctors in a rural province in cambodia. (May 2019) - McGrath, A; Prak, M; Reidel, A; Vanna, D; Sopheak, N; Gborie, I; Leng, D; Turner, C
Abstract : Introduction: The neonatal mortality rate (NMR) in Cambodia is 18 per 1000 births. The NMR in rural areas is higher, with a reported rate of 25 per 1000 in the province being studied. A large-scale programme 'The Saving Babies Lives Programme' is currently being piloted to decrease neonatal deaths in Cambodia. To achieve this, the implementation of a training programme tailored to specific needs was deemed necessary to ensure a sustainable improvement strategy. Methods: National and international guidelines and teaching materials were reviewed with regards to core teaching topics and the level of care to be provided at each facility. To assess areas requiring the most input, a pre-designed assessment tool adapted from a KAP design (Knowledge, Attitudes and Practice) was undertaken in all healthcare facilities in the province being studied (45 health facilities, 1 hospital). This comprised of two parts, a questionnaire answered by staff and a section answered by the research team auditing the facility. The research team members were trained as instructors and mentors. Results: A two and three-tier neonatal training programme was developed, depending on staff type (midwife, nurse or doctor) comprising of a classroom-based residential component, shadowing at a tertiary neonatal facility and an extensive mentorship period at each facility. Lectures and tutorial materials were prepared along with assessments and logbooks, tailored to topics and conditions commonly encountered and resources available locally. Materials were written in English and translated into Khmer. Where resources were deficient, plans to supply equipment were put in place (for example for neonatal resuscitation). Development of a neonatal care unit was commenced. Conclusions: A comprehensive multiple-tier neonatal training programme was developed and adapted to specific needs for implementation in rural Cambodia. Assessment during and following completion of the programme will evaluate its success and monitor for changing needs.